Legal Certainty for Consumers of Tapak House Based on Purchase Binding Agreements with Pre Project-Selling System - Suyanto, Suyanto; Subekti, Subekti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The Purchase Binding Agreement (PBA) was born as a result of the existence of several requirements stipulated by law in the sale of houses Tapak, have not yet been fulfilled which ultimately inhibits the completion of the sale transaction. To still be able to buying and selling houses Tapak then the parties agreed to buy and sell will be done after the certificate is taken care of or after the price is paid in full and to keep the agreement, it is still implemented well while the requirements requested can still be taken care of then the parties poured the initial agreement in the PBA. However, not yet sale and purchase of houses Tapak through the Deed of Sale in front of Land Deed Making Official required by law can be detrimental the consumer, if the consumer has paid the sale price, ownership the right to housing has not yet been transferred from the agents of development because it has not been fulfilled-conditions requested by law. This research purpose was to explain the legal certainty for consumers in buying and selling houses Tapak based on the Purchase Binding Agreement with the pre project selling system after it occurs real surrender by development actors. Sale and purchase of houses Tapak based on the Purchase Binding Agreement with the pre system project selling is a solution when the provisions in the Civil Code differ from the provisions contained in the Basic Regulations Agrarian Principles, but this can cause uncertainty the law for consumers when the home buyer consumers have paid the price in full the house but the development agent did not submit proof of ownership rights to consumers of Tapak house buyers. Tapak house buyers have a Letter of Engagement Agreement for Sale and Purchase so that when the site is submitted to consumers are buyers of Tapak houses by development actors, so the position of consumers is not clear. Consumers who buy houses Tapak are not the recipients of power of attorney development not as a landlord tenant. This is what gives rise legal uncertainty.